FISIOLOGIA E PRODUÇÃO DO FEIJOEIRO SOB AÇÃO DAS TINTURAS DE Ligustrum lucidum E Hedychium coronarium NO MANEJO DA ANTRACNOSE - SANTOS, REGINA LOPES DOS (2016)
Anthracnose, caused by Colletotrichum lindemuthianum in common bean, can cause major losses in production. This study aimed to evaluate the effect of application of Ligustrum lucidum W.T.Aiton tincture and Hedychium coronarium J. König, control/management of anthracnose in the greenhouse. It is this the influence of the application of tincture L. lucidum and H. coronarium in the production of bean cultivar IPR-Tuiuiu, changes in pigment content and parameters of Chlorophyll fluorescence before and after application of tincture, and the severity anthracnose. Two experiments were conducted in completely randomized design (CRD) with 5 treatments and 3 replications and treatments: H2O (negative control); fungicide Mancozeb (positive control); 10% (T 10%); 20% (T 20%) and 30% (T 30%) of L. lucidum tincture and the same treatments for the experiment with H. coronarium tincture, the data were evaluated by Gamma distribution, using the statistical program Setting R and R Studio (R Core Team, 2015) .The lowest AUDPC values were observed in the application of H. coronarium tincture, which may indicate that this tincture acted in controlling anthracnose ,. L. lucidum had no effect on disease. The yield components were affected, with the application of 30% of both tinctures led to elevation in the number of pods and therefore the MMG and production. There have been changes in the levels of chlorophyll and carotenoid, experiencing a decrease 48h after inoculation of the pathogen. Observed increase in fluorescence parameters (F, F'm, F'v, F'q, Y (II) and ΦII.) With application of tinctures and Mancozeb both L. lucidum and H. coronarium 20% and a decrease in F'm, F'v, F'q, Y (II) ΦII, F'v / F'm, F'q / F'v and RFD. These evaluations can detect changes within the sheet, demonstrating the potential use of chlorophyll fluorescence in the management and diagnosis of diseases.